Failure analysis and reliability assessment of gold-plated fuzz buttons in elevated temperature - Zhang, L.; Wang, S.; Chen, X.; Guo, J.; Xu, L.; Ling, S.; Zhang, X. (Microelectronics and reliability, 2025)
Gold-plated electrical contacts are widely used in electrical and electronic systems to provide high-quality and reliable connections with minimal signal distortion or power loss. Many studies have been conducted on the failure analysis of gold-coated contacts in high-temperature environments. However, fuzz buttons, as one of the typical end-face contacts, have been less studied. This paper presents an experimental method to analyze the effects of elevated environmental temperatures on the performance of gold-plated fuzz buttons. The results show that the natural length and compression force of fuzz buttons were both shortened and reduced after the elevated temperature tests. Quantitative analysis of the microstructural changes in the test samples was conducted using characterization techniques such as optical microscopy, scanning electron microscopy (SEM), and focused ion beam (FIB) technology. The findings indicate that a large number of twin structures disappeared, the size of the precipitated phases increased, and the dislocation density decreased, leading to a reduced ability of fuzz buttons to resist plastic deformation and resulting in stress relaxation. Furthermore, a nonlinear Wiener stochastic process was used to model the degradation path of the test samples, while the generalized Eyring model was employed to describe the relationship between sample lifetimes and high temperatures. Using the maximum likelihood estimation (MLE) method, the model parameters were estimated from the integral statistics of all performance degradation data, successfully predicting the reliability of the fuzz buttons. •The high temperature has a substantial effect on the natural length and compression force.•From the perspective of material mechanism, a large No. of twins evolve into a lath structures.•The size of precipitated phase increases, and the second phase undergoes growth and coarsening, meanwhile, the dislocations density decreases.•The ability to resist plastic deformation decreased, stress relaxation occurred.•The time required to achieve contact failure decreases with the increases of temperatures